Determinants of antenatal care use in nine sub-Saharan African countries: a statistical analysis of cross-sectional data from Demographic and Health Surveys. Issue 2 (11th February 2022) - Andegiorgish, Amanuel Kidane; Elhoumed, Mohamed; Qi, Qi; Zhu, Zhonghai; Zeng, Lingxia
Abstract : Objective: To explore the factors associated with antenatal care (ANC) visits. Design: A secondary data analysis from cross-sectional studies was conducted. Setting: Sub-Saharan Africa. Participants: 56 002 women aged 15–49 years in Ghana (3224), Kenya (10 981), Malawi (9541), Namibia (2286), Rwanda (4416), Senegal (6552), Tanzania (5536), Uganda (7979) and Zambia (5487) were analysed. Outcomes: 4 + ANC visits. Results: Overall, 55.52% (95% CI: 55.11% to 55.93%) of women made 4 + ANC visits. The highest 4 + ANC visits were in Ghana (85.6%) and Namibia (78.9%), and the lowest were in Senegal (45.3%) and Rwanda (44.5%). Young women 15–19 years had the lowest uptake of 4 + ANC visits. Multivariable analysis indicated that the odds of 4 + ANC visits were 14% lower among women from rural areas compared with those living in towns (adjusted OR (AOR) 0.86; 95% CI: 0.81 to 0.91). This difference was significant in Kenya, Malawi, Senegal and Zambia. However, in Zambia, the odds of 4 + ANC visits were 48% higher (AOR 1.48; 95% CI: 1.2 to 1.82) among women from rural compared with urban areas. Women with higher educational level had more than twofold higher odds of 4 + ANC visits in seven of the nine countries, and was significant in Kenya, Malawi, Rwanda and Zambia. Compared with the poorest household wealth category, odds of 4 + ANC visits increased by 12%, 18%, 32% and 41% for every 20% variation on the wealth quantile. Women in their first-time pregnancy had higher odds of 4 + ANC visits compared with others across all countries, and women who had access to media at least once a week had a 22% higher probability of 4 + ANC visits than women who had no access to media (AOR 1.22, 95% CI: 1.15 to 1.29). Conclusion: The number of ANC visits was considered to be inadequate with substantial variation among the studied countries. Comprehensive interventions on scaling uptake of ANC are needed among the low-performing countries. Particular attention should be given to women of low economic status and from rural areas.